2022
DOI: 10.1038/s41467-021-27763-x
|View full text |Cite
|
Sign up to set email alerts
|

A cortical cell ensemble in the posterior parietal cortex controls past experience-dependent memory updating

Abstract: When processing current sensory inputs, animals refer to related past experiences. Current information is then incorporated into the related neural network to update previously stored memories. However, the neuronal mechanism underlying the impact of memories of prior experiences on current learning is not well understood. Here, we found that a cellular ensemble in the posterior parietal cortex (PPC) that is activated during past experience mediates an interaction between past and current information to update… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 46 publications
(58 reference statements)
0
14
0
Order By: Relevance
“…The PPC serves as a cortical integration site for hippocampally generated allocentric spatial information and egocentric spatial orientation to permit goal-directed navigation ( 19 , 35 37 ). Further, memory reactivation during sleep has been observed in the parietal cortex as in the PFC ( 33 , 38 ), and the importance of PPC-PFC pathway for memory updating was recently highlighted ( 39 ). Therefore, the other behaviors may also elicit sleep-related consolidation effects, but these may not involve the PPC due to absence of goal-directed behavior and because the Plusmaze is the only task of the three that utilized a compartment structure.…”
Section: Discussionmentioning
confidence: 99%
“…The PPC serves as a cortical integration site for hippocampally generated allocentric spatial information and egocentric spatial orientation to permit goal-directed navigation ( 19 , 35 37 ). Further, memory reactivation during sleep has been observed in the parietal cortex as in the PFC ( 33 , 38 ), and the importance of PPC-PFC pathway for memory updating was recently highlighted ( 39 ). Therefore, the other behaviors may also elicit sleep-related consolidation effects, but these may not involve the PPC due to absence of goal-directed behavior and because the Plusmaze is the only task of the three that utilized a compartment structure.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the effect of anesthesia on retrograde amnesia, we used sevoflurane treatment combined with a hippocampus-dependent memory task: the CPFE paradigm ( Ghandour et al, 2019 ; Ohkawa et al, 2015 ; Rudy and O'Reilly, 2001 ; Schiffino et al, 2011 ; Suzuki et al, 2022 ). In this paradigm ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To test this hypothesis, we assessed the effect of sevoflurane, a volatile general anesthetic, on memory function using a hippocampus-dependent memory task, context pre-exposure facilitation effect (CPFE) paradigm ( Fanselow, 1990 ; Ghandour et al, 2019 ; Ohkawa et al, 2015 ; Rudy and O'Reilly, 2001 ; Schiffino et al, 2011 ; Suzuki et al, 2022 ). In the CPFE paradigm mice have to learn the association of context information presented first with foot shock experience delivered later.…”
Section: Introductionmentioning
confidence: 99%
“…Silencing the PPC specifically during the inter-trial interval affected the behavioral performance of rats (Akrami et al, 2018; Hwang et al, 2017), whereas silencing during the stimulus presentation did not affected performance. The PPC is also reciprocally connected to hippocampus via entorhinal and retrosplenial cortices (Save and Poucet, 2009; Whitlock et al, 2008) and to basolateral amygdala via the anterior cingulate cortex (Suzuki et al, 2022), giving fast access to the different memory hubs. Khodagholy et al(Khodagholy et al, 2017) showed coupling of PPC and hippocampal ripples that strengthen in non-REM sleep after rats learned a spatial exploration task, further indicating that RL may relay history information from subcortical memory hubs to cortex.…”
Section: Discussionmentioning
confidence: 99%
“…But do these areas that participate in the learning process also carry history information? Encoding of history information has been reported mainly in higher order cortical areas such as the posterior parietal cortex (PPC) (Akrami et al, 2018;Harvey et al, 2012;Hwang et al, 2017;Morcos and Harvey, 2016;Suzuki et al, 2022) , retrosplenial cortex (Hattori et al, 2019;Vann et al, 2009) and prefrontal cortex (Banerjee et al, 2020;Johnson et al, 2016;Kawai et al, 2015;Sul et al, 2010;Tsutsui et al, 2016) , but also to a smaller extent in lower-order primary sensory areas such as BC (Banerjee et al, 2020;Chéreau et al, 2020;Rodgers et al, 2021). There is still a debate on which areas link history information with the learning process.…”
Section: Introductionmentioning
confidence: 99%